The effect of peritoneal gas drain on postoperative pain in benign gynecologic laparoscopic surgery: a double-blinded randomized controlled trial controlled trial - Tharanon C; Khampitak K (Dove Medical Press, 2016)
Chantip Tharanon, Kovit Khampitak Department of Obstetrics and Gynecology, Srinagarind Hospital, Khon Kaen University, Khon Kaen, Thailand Objectives: To compare the effect of peritoneal gas drain on postoperative pain in benign gynecologic laparoscopic surgery and the amount of postoperative analgesic dosage.Methods: The trial included 45 females who had undergone operations during the period December 2014 to October 2015. The patients were block randomized based on operating time (<2 and ≥2 hours). The intervention group (n=23) was treated with postoperative intraperitoneal gas drain and the control group (n=22) was not. The mean difference in scores for shoulder, epigastric, suprapubic, and overall pain at 6, 24, 48 hours postoperatively were statistically evaluated using mixed-effect restricted maximum likelihood regression. The differences in the analgesic drug usage between the groups were also analyzed using a Student’s t-test. The data were divided and analyzed to two subgroups based on operating time (<2 hours, n=20; and ≥2 hours, n=25).Results: The intervention had significantly lower overall pain than the control group, with a mean difference and 95% confidence interval at 6, 24, and 48 hours of 2.59 (1.49–3.69), 2.23 (1.13–3.34), and 1.48 (0.3–2.58), respectively. Correspondingly, analgesic drug dosage was significantly lower in the intervention group (3.52±1.47 mg vs 5.72±2.43 mg, P<0.001). The three largest mean differences in patients with operating times of ≥2 hours were in overall pain, suprapubic pain at 6 hours, and shoulder pain at 24 hours at 3.27 (1.14–5.39), 3.20 (1.11–5.26), and 3.13 (1.00–5.24), respectively. These were greater than the three largest mean differences in the group with operating times of <2 hours, which were 2.81 (1.31–4.29), 2.63 (0.51–4.73), and 2.02 (0.68–3.36). The greatest analgesic drug requirement was in the control group with a longer operative time.Conclusion: The use of intraperitoneal gas drain was shown to reduce overall postoperative pain in benign gynecologic laparoscopic surgery. The effects were higher in patients who had experienced longer operating times. Keywords: laparoscopic surgery, intraperitoneal gas drain, postoperative pain, gynecology